Church diplomacy and inter-orthodox relations in the era of persecution: the experience of the holy Patriarch Tikhon - Aleksandr Mazyrin (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2024)
Article on the views and actions of Patriarch Tikhon (Bellavin) of Moscow and All Russia in the field of Inter-Orthodox relations in 1917–1925. It is shown that this direction was not a priority for His Holiness Tikhon in the context of full-scale persecution of the Russian Orthodox Church, especially since he had minimal opportunities to maintain contacts with other Local Churches. Unlike the leaders of a number of other Churches (Constantinople, Romanian, etc.), St. Tikhon in his ministry was guided not by political or nationalist motives, but by spiritual, moral and pastoral ones, adhering to the evangelical and canonical norms of the Orthodox Church. He sought to resolve controversial issues peacefully and amicably (for example, in the case of Georgian autocephaly), but did not always meet with a reciprocal desire to act in the same way. He was alien to any kind of jurisdictional selfishness. The main thing for him was the preservation of loyalty to Orthodoxy on the part of the multinational flock of the Russian Church. This, in particular, determined his rejection of the idea of Polish autocephaly. The warmest relations under Patriarch Tikhon were with the Serbian and Antiochian Orthodox Churches. Most of all, problems arose in the Constantinople direction, due to the extreme politicization of the Fanar and its special tendency to trample on the moral and canonical norms of the Orthodox Church.